2005
DOI: 10.2337/diabetes.54.9.2795
|View full text |Cite
|
Sign up to set email alerts
|

Variation in the eNOS Gene Modifies the Association Between Total Energy Expenditure and Glucose Intolerance

Abstract: Endothelium-derived nitric oxide (NO) facilitates skeletal muscle glucose uptake. Energy expenditure induces the endothelial NO synthase (eNOS) gene, providing a mechanism for insulin-independent glucose disposal. The object was to test 1) the association of genetic variation in eNOS, as assessed by haplotype-tagging single nucleotide polymorphisms (htSNPs) with type 2 diabetes, and 2) the interaction between eNOS haplotypes and total energy expenditure on glucose intolerance. Using multivariate models, we tes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
1
1

Year Published

2006
2006
2013
2013

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 53 publications
0
13
1
1
Order By: Relevance
“…Thus, we were unable to confirm a relationship between the rs1799983 genotype and type 2 diabetes, previously described in a small European study [38]. Furthermore, we could not replicate an association between NOS3 haplotypes and the prevalence of type 2 diabetes [39]. Again, selective reporting of positive findings amongst small studies is the most plausible explanation of these discrepancies.…”
Section: Discussioncontrasting
confidence: 60%
“…Thus, we were unable to confirm a relationship between the rs1799983 genotype and type 2 diabetes, previously described in a small European study [38]. Furthermore, we could not replicate an association between NOS3 haplotypes and the prevalence of type 2 diabetes [39]. Again, selective reporting of positive findings amongst small studies is the most plausible explanation of these discrepancies.…”
Section: Discussioncontrasting
confidence: 60%
“…On the other hand, de Syllos suggested that haplotype 112 was protective of T2DM, as it was present at low frequencies among T2DM patients 14 . While not addressing DR, Franks demonstrated the select association between specific eNOS haplotypes and T2DM and associated conditions (energy metabolism) 19 . The differences in eNOS haplotype distribution among Tunisian Arabs with other populations may be explained by ethnic variation in the eNOS haplotype distribution, highlighted by the high prevalence of the 111 haplotype among Asians (77%) compared to other ethnic groups (46%) 20 …”
Section: Discussionmentioning
confidence: 99%
“…obesity, elevated fasting glucose levels, dyslipidemia, hypertension) and urinary cGMP excretion, suggesting that a reduction of NO bioactivity concurs with these CV risk factors [33]. Moreover, genetic variations of eNOS gene influenced energy expenditure, severity of glucose intolerance and risk of developing type II diabetes [34]. Chronic (alternate-day) administration of TAD in men with ED had improved endothelial function as indicated by marked changes in serum markers of endothelial function, increased insulin levels and a robust decrease in the inflammatory marker, high sensitivity C-reactive protein (hs-CRP) [35].…”
Section: Introductionmentioning
confidence: 99%